Frankenstein was a vegetarian : essays on food choice, identity, and symbolism. - Jones, Michael Owen (University Press of Mississippi, 2022)
This resource tackles topics often overlooked in foodways. Michael Owen Jones explains how we communicate through what we eat, the connection between food choice and who we are or want to appear to be, the ways that many of us self-medicate moods with foods, and the nature of disgust.